Ruptured Baker’s Cycst Mimicking the Symptoms of Deep Vein Thrombosis in a Rheumatoid Arthritis Patient - Demet Göçmen Demir; Lale Altan; Nuray Dıraz (Archives of Rheumatology, 2008)
A 50- year- old male patient who had a diagnosis of rheumatoid arthritis was admitted to our clinic with the complaint of sudden onset of severe pain and swelling in his right knee and calf. An initial diagnosis of deep vein thrombosis was made, however, ultrasound imaging revealed bilateral popliteal Baker’s cysts. The cyst on the right side was ruptured. Both of the cysts were aspirated. Concomitant occurrence of rheumatoid arthritis and Baker’s cyst which could be confused with deep venous thrombosis was discussed in this case presentation (Rheumatism 2008 23: 63-5)